Dialogue of Diversity: Mapping Emotional Nuance and Social Differences through Expressive Speech Acts - Suryatama, Syachrukh Ramadhan (CV. Era Digital Nusantara, 2025)
This research explores the mapping of emotional nuance and social differences through expressive speech acts in the narrative-driven video game Assassin’s Creed: Odyssey. Focusing on the protagonist, Alexios, the study aims to identify the types of expressive language used and analyze how these linguistic choices contribute to the depiction of diverse social interactions and character development. Using a qualitative approach, the study examines fifty selected utterances from the game’s dialogue based on the speech act theories of Austin (1962), Searle and Vanderveken (1985), and Leech (1983). The findings reveal ten distinct types of expressive speech acts: protesting, complaining, thanking, boasting, condoling, greeting, complimenting, apologizing, lamenting, and congratulating. Protesting emerged as the most dominant type (40%), highlighting Alexios’s frequent reactions to social injustice, betrayal, and unfair treatment within the game’s complex world. Furthermore, the analysis identifies the conflictive function (58%) as the primary illocutionary mode, followed by convivial and collaborative functions. These results suggest that expressive speech acts serve as a vital mechanism for portraying how an individual navigates social inequality and diverse group dynamics. Rather than focusing on action, the game uses nuanced dialogue to communicate social meanings and the complexities of human relationships. This study highlights the role of digital storytelling in reflecting social differences and individual agency, illustrating how language shapes the protagonist's journey through a fragmented and diverse society.